SURVEI KESEHATAN TENGGOROKAN SISWA SD INPRES 10/73 PANDU - Theno, Giovanny G.; Tamus, Agustien Y.; Tumbel, R. E. C. (e-CliniC, 2016)
Abstract: Due to modernization, people tend to become careless about the importance of health, therefore, health problems increase; one of them is throat disease. Tonsils consist of lymphoid tissue and have important function against infection either through the air or food. This study aimed to obtain the throat health status of students at Inpres 10/73 Pandu Elementary School. This was a descriptive observational study with a cross sectional approach. Respondents were 18 students of Inpres 10/73 Pandu Elementary School, consisted of 8 boys and 10 girls. The results showed that all respondents had normal color tonsils. On examination of the tonsil surfaces, 16 children (88.89%) had normal results and 2 children (11.11 %) had pathological results. On examination of the tonsil sizes, 13 children (72.22%) had normal results and 5 children (27.78%) had pathological results. On examination of the pharynx, 16 children (88.89%) had normal results and 2 children (11.11%) had pathological results. Conclusion: Most of the students of Inpres 10/73 Pandu Elementary School had normal throat health statusKeywords: health survey, throat examinationÂ Abstrak: Seiring dengan perkembangan zaman, kepedulian terhadap kesehatan menjadi menurun sehingga muncul berbagai masalah kesehatan antara lain penyakit tenggorokan. Tonsil merupakan kumpulan jaringan limfoid yang berfungsi penting dalam pertahanan tubuh terhadap infeksi baik melalui udara maupun makanan. Penelitian ini bertujuan untuk mendapatkan gambaran kesehatan tenggorok pada siswa-siswi Sekolah Dasar Inpres 10/73 Pandu. Penelitian ini menggunakan metode deskriptif survei dengan pendekatan potong lintang. Responden ialah siswa-siswi Sekolah Dasar Inpres 10/73 Pandu sejumlah 18 anak, terdiri dari 8 laki-laki dan 10 perempuan. Pada hasil pemeriksaan warna tonsil didapatkan semuanya normal. Pada pemeriksaan permukaan tonsil didapatkan 16 anak (88,89%) memiliki hasil normal dan 2 anak (11,11%) lainnya patologis. Pada pemeriksaan ukuran tonsil, didapatkan 13 anak normal (72,22%) dan 5 anak (27,78%) patologis. Pada pemeriksaan faring, didapatkan 16 anak ((88,89%) normal dan 2 anak (11,11%) patologis. Simpulan: Sebagian besar hasil pemeriksaan pada pada siswa-siswi Sekolah Dasar Inpres 10/73 Pandu adalah normalKata kunci: survei kesehatan, pemeriksaan tenggorok